From Green Revolution to Agricultural Transformation: The Case of Short Duration Rice Varieties in Bangladesh - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2018)
Most of the world’s extreme poor are located in Sub-Saharan Africa (SSA) and South Asia (SA), live in rural areas, and depend on agriculture as their main source of income. A vast majority are smallholder farmers, and improving their incomes can help them escape poverty. In areas where a Green Revolution-style intensification may not be an option, an alternative is to diversify income sources in agriculture by changing farming systems to introduce higher value crops and to extend labor calendars to reduce periods of forced idleness. When looking at the origins of rural poverty, it is indeed notable that lack of opportunities to use labor productively during an important fraction of the year is highly correlated with low per capita consumption. This is what the Agricultural Transformation tries to achieve.